Analysis of Variation of Valve Gap Size on Power and Torque of a Four-stroke Motorcycle - Widiyatmoko; Mike Elly Anitasari; Ari Fajar Isbakhi (Politeknik Piksi Ganesha Indonesia, 2023)
This study aims to analyze changes in valve clearance on engine power and torque. The subjects in this study were four-stroke motorcycles with a cylinder capacity of 100 cc. The stages of the research included: 1) Preparation by adjusting the size of the inlet and outlet valve gaps with the dimensions in millimeters being 0.03, 0.05, and 0.07; 2) Testing using a dyno test; 3) The conclusion is based on the results of the dyno test tool print out data. Research results: 1) The maximum engine power achieved at the valve clearance size of 0.03 mm and 0.05 mm is 4.5 hp. Maximum engine power at 0.03 mm valve clearance is achieved at 6.42 rpm, while 0.05 mm valve clearance is achieved at 6.39 rpm; 2) The highest maximum engine torque among the three variations in valve clearance size, is 0.03 mm, which is 5.92 N.m at 3.081 rpm; 3) The size of the valve gap that is not by the standard specifications will significantly affect the power and torque of the engine.